Targeting NLRP3 Inflammasome Alleviates Synovitis by Reducing Pyroptosis in Rats with Experimental Temporomandibular Joint Osteoarthritis. (23rd November 2022) - Xin, Yinzi; Wang, Wei; Mao, Enyu; Yang, Hefeng; Li, Song
Abstract : The mechanism of temporomandibular joint osteoarthritis (TMJOA), which leads to the final erosion of cartilage and subchondral bone, has been widely demonstrated, but still not clearly elucidated. Many studies have pointed that NLRP3-mediated inflammation played a vital role in degenerative diseases. However, its interaction with synovitis of TMJOA has remained poorly investigated. In our study, we explored the role of NLRP3 inflammasome in TMJOA synovitis and the therapeutic potential of caspase-1 and NLRP3 inhibitors. By establishing a rat TMJOA model, we found that NLRP3 was upregulated in synovial tissue of TMJOA. It was involved in the progress of a programmed cell death called pyroptosis, which was caspase-1 dependent and ultimately triggered inflammatory mediator interleukin IL-1 β release. Treatment with Ac-YVAD-cmk and MCC950, inhibitors targeting caspase-1 and NLRP3, respectively, significantly suppressed pyroptosis in TMJOA synovial tissue. Then, a macrophage- and fibroblast-like synoviocyte (FLS) cocultured model further verified the above results. Macrophage somehow promoted FLS pyroptosis in this study. Our results suggested that the NLRP3 inflammasome-mediated pyroptosis participated in synovial inflammation of TMJOA. Interfering with the progress could be a potential option for controlling TMJOA development.